Ability of Fractional Flow Reserve to Predict Restenosis After Superficial Femoral Artery Stenting. (December 2016) - Kobayashi, Norihiro; Hirano, Keisuke; Yamawaki, Masahiro; Araki, Motoharu; Sakai, Tsuyoshi; Takimura, Hideyuki; Sakamoto, Yasunari; Mori, Shinsuke; Tsutsumi, Masakazu; Takama, Takuro; Honda, Yohsuke; Tokuda, Takahiro; et al.
Purpose: To evaluate the clinical efficacy of poststenting fractional flow reserve (FFR) in terms of predicting restenosis in superficial femoral artery (SFA) disease.Methods: This prospective, single-center, nonrandomized study enrolled 48 patients (mean age 76±9 years; 38 men) with 51 SFA lesions from July 2013 to June 2014. Mean FFR (distal mean pressure/proximal mean pressure) and systolic FFR (distal systolic pressure/proximal systolic pressure) were calculated, and the relationship between these FFR values and restenosis at 12 months was investigated using receiver operating characteristic (ROC) curve analysis.Results: Poststenting FFR was significantly lower in the restenosis group (poststenting mean FFR 0.85±0.07 vs 0.93±0.05, p=0.001; poststenting systolic FFR 0.76±0.14 vs 0.87±0.08, p=0.015). The area under the ROC curve for restenosis in poststenting mean FFR was higher, but not statistically significant, than that in poststenting systolic FFR (0.84 vs 0.74, p=0.08). The best poststenting mean FFR cutoff value for predicting restenosis was 0.92 (sensitivity 0.64, specificity 0.91). The 4.5% restenosis rate at 12 months in the high (>0.92) poststenting mean FFR group was significantly lower (35.7%, p=0.008) than in the low (≤0.92) poststenting mean FFR group.Conclusion: Poststenting mean FFR is useful for predicting restenosis in SFA disease.